Coastal wetlands of the world : geology, ecology, distribution and applications - Scott, D. B.; Frail-Gauthier, Jennifer; Mudie, Petra J. (Cambridge : Cambridge University Press, 2014)
Salt marshes and mangrove forests, the intertidal wetlands of the world's coastlines, provide key ecological services to all areas of the globe, and are vital sinks and sources in carbon budgets.
Keywords: Wetland ecology; Wetland conservation; Coasts; Coastal ecology